Evaluation of vannamei shrimp farming management: A case study at the Prigi Marine Aquaculture Installation, Indonesia - Savirah, Annisa Nur; Halim, Abdul; Ariwibowo, Dimas Agung (UIN Sunan Ampel Surabaya, 2025)
This study investigates the growth performance, health monitoring, and management practices in the farming of vannamei shrimp at the Prigi Marine Aquaculture Installation (IBL Prigi), Indonesia. Sampling was conducted from Days of Culture (DOC) 40 to harvest, with data on shrimp growth, Average Body Weight (ABW), and size recorded regularly. The results showed consistent growth in shrimp from March to May 2024, with ABW increasing from 1.93 grams to 18 grams over the study period. However, survival rates (SR) were notably low, with Pond 1 at 24.51% and Pond 2 at 43.97%, suggesting potential issues in shrimp survival. The Feed Conversion Ratio (FCR) ranged from 1.73 to 1.93, indicating inefficiencies in feed utilization, especially in Pond 1. Health monitoring revealed challenges such as molting failure, reduced appetite, and softshell conditions in Pond 1, while Pond 2 experienced fewer health issues. Disease management involved feed adjustments and the use of minerals. Wastewater was managed through sedimentation at the wastewater treatment plant, contributing to sustainable practices. Overall, while growth trends were positive, improvements in survival rates, feed efficiency, and health management are necessary for optimizing shrimp production at IBL Prigi.